-3(3m-10)-7=-5(5m+1)+3m

Simple and best practice solution for -3(3m-10)-7=-5(5m+1)+3m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(3m-10)-7=-5(5m+1)+3m equation:



-3(3m-10)-7=-5(5m+1)+3m
We move all terms to the left:
-3(3m-10)-7-(-5(5m+1)+3m)=0
We multiply parentheses
-9m-(-5(5m+1)+3m)+30-7=0
We calculate terms in parentheses: -(-5(5m+1)+3m), so:
-5(5m+1)+3m
We add all the numbers together, and all the variables
3m-5(5m+1)
We multiply parentheses
3m-25m-5
We add all the numbers together, and all the variables
-22m-5
Back to the equation:
-(-22m-5)
We add all the numbers together, and all the variables
-9m-(-22m-5)+23=0
We get rid of parentheses
-9m+22m+5+23=0
We add all the numbers together, and all the variables
13m+28=0
We move all terms containing m to the left, all other terms to the right
13m=-28
m=-28/13
m=-2+2/13

See similar equations:

| -16+4=-4x | | 4x-33-9x=2+x | | 1.46g-3=8.65 | | 14x+15=42+4x | | 7x+4=102 | | 3+8+x=6+5 | | 11x+1=5x-2 | | –10q=–7q−9 | | -3m+2-4m=-7m+4 | | -10v+10=-9v+9 | | -1+5x=-(-5x+8)+5 | | n−9.02=3.85 | | 4(5x-3)+7=-3 | | (3,6)m=5 | | −2(−14)=−114x(−14) | | 9.32=2w | | 15-2(3x+5)=6(5+x) | | 2-1/14x=0 | | 8v^2-24v=0 | | 0.15(x+1,000)=6,750 | | 23=-4x+2+1x | | 13x+13=26 | | 8^2-24v=0 | | 12=5x-(4x-1) | | y=2-0.4^2 | | 190.60=5(0.06m+29.80+0.10(29.80)) | | –9(t+–15)=72 | | 6y+(16-y)=-(-4y-16)+y | | 9x+7x-8x-5=19 | | 6/20=x/180 | | 30-(7x-2x)=3(x+24)-8x | | r8=-3 |

Equations solver categories